Perfil de erupção de pacientes portadores da síndrome de zika congênita - Pereira, Taissa Andreza Alves (2018)
Congenital Zika Syndrome (SZC) it’s a condition where infants are afected by Zika virus during the first trimester of pregnancy, discovered after a significant increase in the number of children born with microcephaly in Brazil after an outbreak of Zika infection in 2015. Dental eruption is part of child development and growth and indicates a series of biological occurrences that can be influenced and have its course altered. The objective of this study was to evaluate the dental eruption in children with SZC, qualitatively and quantitatively, including possible associations between eruption event, chronological age and sex. Nineteen kids diagnosed with SZC were evaluated in 4 moments at Fortaleza (CE) in a prospective observational study. Data were tabulated and later submitted to statistical analysis (p <0.001). Initially the volunteers had on average 10.32 months, 63.20% (n = 12) of the sample having total absence of deciduous teeth. In the last evaluation, the average age was 30.68 months, 18 babies with at least 1 molar erupted. during all the mutirões, boys had more teeth than the girls. In mutirões 3 and 4 all volunteers had at least 1 erupted tooth. The comparison between the number of teeth erupted in infants and between the age of the population evaluated during the mutirões showed a significant difference (p <0.001). No significant correlation was observed when correlating the age of the babies in each group with the totals of erupted teeth. It was concluded that boys’ deciduous teeth eruption precedes girls and there is a delay in the beginning of the dental eruption in the babies with SZC, when compared to the previously described patterns in the literature.